Influence of Base Tangent Length Deviation on Nonlinear Dynamics Characteristic of Helical Gear System - Yuxi Ma; Siyu Chen; Jinyuan Tang; Weitao Chen (Jixie chuandong)
Abstract The design of the base tangent length deviation is generally selected according to the design manual. The study of the relationship between the base tangent length deviation design and the meshing dynamics performance has not been reported in literature. Through deducing the formula for calculating the meshing stiffness and meshing clearance under the deviation of the common normal line， the dynamics model of a 12-DOF helical gear transmission system with nonlinear factors such as time-varying mesh stiffness and backlash is established. Four base tangent length deviation groups under 6-level precision are considered， and the peak-to-peak curve， amplitude-frequency response and root mean square curve of transmission error of the system are obtained by calculation， the design flow of optimal base tangent length deviation is given. The analysis result shows that， the influence on the system at low speed is stable， when the system is at high speed， it will jump and enter chaos. The base tangent length deviation has a significant influence on the impact characteristics of the gear pair system， and an appropriate increase in the base tangent length deviation can improve the impact of the system. The analysis found that the gear pair system is the best dynamic characteristic in the third base tangent length deviation group. A dynamics evaluation method for the design of base tangent length deviation is provided by the research result， it has reference value for high-performance gear design research.